The lymphatic superficial circumflex iliac vessels deep branch perforator flap: A new preventive approach to lower limb lymphedema after groin dissection‐preliminary evidence. Issue 6 (17th December 2016) - Gentileschi, Stefano; Servillo, Maria; Garganese, Giorgia; Fragomeni, Simona; De Bonis, Francesca; Cina, Alessandro; Scambia, Giovanni; Salgarello, Marzia
Abstract: Objective: Groin dissection is the procedure with the highest risk of lower limb lymphedema.As lymph stasis causes irreversible alterations to the limb over time, therapies should be administered in early stages, or better yet, lymphatic drainage impairment should be prevented.We developed a new preventive approach to lymphedema after groin dissection, and we report our preliminary experience. Patients and Methods: We enrolled 5 patients undergoing bilateral groin dissection for vulvar cancer. Preoperative study of lower limbs lymphatic function was obtained by lymphoscintigraphy, with lymphatic transport index, indocyanine green (ICG) lymphography, and volume measurement with lower extremity lymphedema (LEL) index calculation. At the end of lymphadenectomy, one groin was closed in the standard way. On the other side, a lymphatic flap pedicled on the distal perforator of the deep branch of the superficial circumflex iliac vessels, was transposed into the groin region. Lymphatic function examination of the limbs was repeated 6 months after surgery. Results: Before surgery no patient showed lymphatic drainage impairment at lymphoscintigraphy or lymphography, LEL index was in every limb lower than 250 (mean: 217.3 ± 13.83). After surgery the limbs treated with the flap showed no pathological swelling, LEL‐index < 250 (mean: 235.4 ± 13.069), linear pattern at lymphography, and normal lymphoscintigraphy. The untreated limbs showed from moderate to severe edema with 265 < LEL‐index < 310 (mean: 283 ± 16.3), diffuse dermal backflow at lymphography and interruption of lymph flow, with dermal backflow, at lymphoscintigraphy. Mean difference between preoperative and postoperative volumes was 64.8 ± 25.1 in the untreated side and 19 ± 11.7 in the side with the flap. The difference between preoperative and postoperative volumes compared between the treated and untreated side was statistically significant ( P  < .01). Conclusion: Our preliminary evidence suggests that this flap can prevent lymphedema after groin dissection. Further studies are necessary to confirm these results.